Multivariate Analysis in Formulation of the Benefit-Cost Index Related to the Sugarcane Production System in the Quirinopolis Municipality Productive Center, Goias, Brazil - Nacife, Jean Marc; Soares, Frederico Antonio Loureiro (International Journal of Business, Economics and Management, 2019)
Food and bioenergy agriculture are growing demands of the global population. The problem of rural production facilities resides in gross revenue and not in issues related to production scale, since the price is determined by the market. The performance measure indicators, whether financial or not, have helped managers to focus their actions on long-term perspectives of sustainable socioeconomic production in rural production facilities. It is proposed to validate an equation model composed of social and economic indicators as a parameter for monitoring the development of sugarcane production in agricultural production facilities by means of multivariate analysis techniques and to characterize the socioeconomic factors different profiles in rural production facilities studied. The methodological approach was quantitative, applying techniques of inferential statistics and multivariate analysis by test for normality, test of the Friedman hypothesis, Categorical Principal Components Analysis, adjustment of multiple linear regression model and profile segmentation. The statistical tests showed statistical significance (P<0.05), CATPCA presented 2 dimensions with Cronbach’s alpha adequate and a linear regression model was adjusted with adequate R2 of 0.90. The results by profile show that the IBCcane was the best of the smallholdings with 24.39 ha-1, (100% of the lessors). The IBCcane by establishments profile was: 424.39 (smallholding); 174.66 (small); 827.34 (medium); and 2,765.96 (large). The multivariate analysis determined the equation validity for the proposed indicators, it was proven that the smallholdings have the best benefit-cost index and the benefit-cost by profile showed that the large ones have a greater financial gain due to the productive scale.